The management of testis cancer. Issue 10 (October 2016) - Clarke, Noel W.; Hoyle, Alex P.
Abstract: Testis cancer is rare but it is the commonest cause of malignancy in young men. Painless testicular masses must be investigated with ultrasound imaging and tumour marker assay before being treated urgently with radical inguinal orchidectomy if suspicion persists. Disease localized to the scrotum is curable with surgery alone in most cases but high risk features in clinical stage 1 disease predict failure in a significant proportion. Such cases need close surveillance or adjuvant intervention therapy following primary surgery. More advanced disease (clinical stage 2 or greater) requires treatment with combination platinum based chemotherapy, usually including, bleomycin, etoposide and cisplatinum (BEP). Post chemotherapy tumour masses are resected surgically when this is possible. Metastatic disease is sub-stratified into low, intermediate and high risk categories based on the extent and location of metastases on cross-sectional imaging and on the level of specific tumour markers according to the European Germ Cell Cancer Collaborative Group (EGCCCG) criteria. This enables use of risk stratified treatment regimens tailored to individual patients according to their disease characteristics. Treatment outcome is excellent overall and this cancer is a modern model for the curable neoplasm. The goal of reducing side effect profiles following treatment and improving outcomes in the high risk metastatic group pose the biggest obstacles in this condition.